Shoulder recovery for head and neck cancer patients after unilateral neck dissection: a pilot exploratory study - Tan, C.; Yeo, P.; Rangabashyam, M.; Omar, A.; Ng, C.; Sultana, R.; Netto, Kevin; Png, M.; Nagadia, R.; Tay, G.; Tan, N.; Iyer, N.; et al. (2022)
An established side-effect of neck dissection (ND) for head and neck (HNC) tumour management includes shoulder dysfunction (SD), which can impact quality of life (QOL). Shoulder strength and range of movement (ROM) are key parameters to be monitored in SD. However, such evaluations are not routinely conducted in the clinical setting. The aim of this study was to evaluate objectively the impact of ND on shoulder functions.